2014
DOI: 10.1007/s00253-014-6197-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of physiological properties of Torulaspora delbrueckii in wine fermentations and its incidence on wine quality

Abstract: This work examines the physiology of a new commercial strain of Torulaspora delbrueckii in the production of red wine following different combined fermentation strategies. For a detailed comparison, several yeast metabolites and the strains implantation were measured over the entire fermentation period. In all fermentations in which T. delbrueckii was involved, the ethanol concentration was reduced; some malic acid was consumed; more pyruvic acid was released, and fewer amounts of higher alcohols were produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
178
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(209 citation statements)
references
References 62 publications
28
178
3
Order By: Relevance
“…Metabolic, chemical and sensory profile studies of non-Saccharomyces yeast fermentations have shown that T. delbrueckii species in particular make a positive contribution toward the flavour of alcoholic beverages (Ciani & Picciotti, 1995;Ciani & Maccarelli, 1998;Jolly et al, 2003a;Van Breda et al, 2013;Belda et al, 2015;Loira et al, 2015;Renault et al, 2015;Chen & Liu, 2016;Renault et al, 2016;Ngqumba et al, 2017). This was further demonstrated in a study conducted by Hernández-Orte et al (2008), in which wines produced with T. delbrueckii had high concentrations of aliphatic lactones and ethyl dihydrocinnamate, imparting sensory notes such as "dried fruit" and "coconut" to the wine.…”
Section: Introductionmentioning
confidence: 71%
“…Metabolic, chemical and sensory profile studies of non-Saccharomyces yeast fermentations have shown that T. delbrueckii species in particular make a positive contribution toward the flavour of alcoholic beverages (Ciani & Picciotti, 1995;Ciani & Maccarelli, 1998;Jolly et al, 2003a;Van Breda et al, 2013;Belda et al, 2015;Loira et al, 2015;Renault et al, 2015;Chen & Liu, 2016;Renault et al, 2016;Ngqumba et al, 2017). This was further demonstrated in a study conducted by Hernández-Orte et al (2008), in which wines produced with T. delbrueckii had high concentrations of aliphatic lactones and ethyl dihydrocinnamate, imparting sensory notes such as "dried fruit" and "coconut" to the wine.…”
Section: Introductionmentioning
confidence: 71%
“…Other authors have reported that other non-Saccharomyces yeast produced lower amounts of higher alcohols than Saccharomyces cerevisiae (Benito et al, 2015a;Clemente-Jimenez et al, 2004;Gobbi et al, 2013;Parapouli et al, 2010;Romano and Suzzi, 1993;Romano, 2003;Zironi et al, 1993). Sometimes low levels of higher alcohols increased the perception the aroma of varietal grape varieties, which was considered a positive effect (Belda et al, 2015). A total higher alcohol concentration of less than 350 mg/L is recommended because a higher concentration gives the wine a disagreeable alcoholic flavor.…”
Section: Volatile Aromasmentioning
confidence: 99%
“…Scientific works about these two species are abundant [7,[39][40][41][42], being the most common non-Saccharomyces species commercially available for wine industry besides Torulaspora delbrueckii strains [10,43,44]. T. delbrueckii showed a low implantation rate in fresh must but, due to its high fermentation power and ethanol tolerance (9-11%), it is one of the non-Saccharomyces yeasts with higher incidence on wine properties and quality.…”
Section: Population Study Rational Use Of Genomic Technologymentioning
confidence: 99%
“…T. delbrueckii is, at present, the most applied non-Saccharomyces yeast in the wine industry. Most of yeast distribution companies have developed T. delbrueckii strains and work, together with researchers, in the gain of knowledge about their physiology and genetic and metabolic regulation in fermentation conditions [10,43,44,58,59].…”
Section: Enzymatic Study Foreseeing the Repercussion Of Yeasts On Wimentioning
confidence: 99%
See 1 more Smart Citation